Target controlled alternative hybridization chain reaction for fluorescent detection of dual mycotoxins - Ma, Qin; Lin, Yiyan; Yang, Yun; Yang, Wenming; Yun, Wen; Zhang, Mingming; Yang, Lizhu (Analytica chimica acta, 2023)
A target controlled alternative hybridization chain reaction (HCR) was developed for fluorescent detection of multiple mycotoxin. Ochratoxin A (OTA) and aflatoxin B1 (AFB1) can bind with their specific aptamer on the gold nanoparticles and cause the releasing of the short DNA sequences. The short DNA sequences can trigger different reaction route of HCR and thus produce two kinds of side-chain sequences. The side-chain sequences can cause the opening of the DNA tweezers and result the recovery of fluorescent signals. Good linear relationships were obtained in the range of 0.06–2 ng/mL (R2 = 0.994) for OTA and 0.005–1 ng/mL (R2 = 0.992) for AFB1 with limit of detection of 0.02 ng/mL for OTA and 0.002 ng/mL for AFB1. Importantly, it showed great sensitivity and excellent selectivity in practical food sample analysis for simultaneous detection of OTA and AFB1. [Display omitted] •An alternative hybridization chain reaction was developed for dual mycotoxins detection.•The hybridization chain reaction route can be controlled by the target.•This strategy shows promising potentials for simultaneous detection of OTA and AFB1.